Correlation of Energy-Protein Consumption with Blood Glucose Levels and Blood Pressure of Primary School Children in Kupang East of Nusa Tenggara Province Participating in School-Feeding Program - Renny Fridieyanti; Vera Uripi; Rizal Damanik (Media Gizi dan Keluarga, 2000)
The Objective of this study was to observe correlation of energy-protein consumption with blood glucose levels and blood pressure of primary school children in Kupang East of Nusa Tenggara province participating in school-feeding program. The result of the study showed that on the day without school feeding 99,6% (pre) and 97% (post) of children had normal blood glucose levels and 86,3% (pre) and 87,2% (post) of children had normal systolic blood pressure but 78,2% (pre) and 68,4% (post) of children had hypotension of diastolic blood pressure. While on the school-feeding day 100% (pre and post) of children had normal blood glucose levels, 85,5% (pre) and 86,8% (post) of children had normal systolic blood pressure and 95,3% (pre) and 95,7% (post) of children had hypotension of diastolic blood pressure. There was 0,4% (pre) and 3% (post) of children had hypoglicemic status. The means of energy-protein consumption indicated that most of the children had a severe deficit of energy-protein intakes. On the day without school-feeding 32,1% and 47,4% of children had a severe deficit of energy-protein intakes. That percentages were raised on the school-feeding day. While on the school-feeding day 49,6% and 57,7% of children had a severe deficit of energy-protein intakes. The Spearman’s analysis showed that between energy-protein intakes and blood glucose levels as well as blood pressure were not significantly correlated.Keyword: consumption, glucose, blood pressure